Analysing the behavioural finance impact of "fake news" phenomena on financial markets: A representative agent model and empirical validation - Bryan Fong (Financial Innovation, 2021)
This paper proposes an original behavioural finance representative agent model, to explain how fake news' empirical price impacts can persist in finance despite contradicting the efficient-market hypothesis. The model reconciles empirically-observed price overreactions to fake news with empirically-observed price underreactions to real news, and predicts a novel secondary impact of fake news: that fake news in a security amplifies underreactions to subsequent real news for the security. Evaluating the model against a large-sample event study of the 2019 Chinese ADR Delisting Threat fake news and debunking event, this paper finds strong qualitative validation for its model's dynamics and predictions.
Keywords: 650; Behavioural finance; Bootstrapping; Event study; Fake news; Representative agent model